Analisis Pengaruh Good Corporate Governance Terhadap Reaksi Investor Pada Perusahaan Perbankan di BEI - Juraida Titin Marliana; Septiatin Rosi Amelia; Ferty Agatha (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2025)
The implementation of Good Corporate Governance (GCG) in the banking sector is a fundamental aspect expected to enhance investor confidence and elicit a positive market reaction. However, the existing empirical gap shows that improved GCG scores are not consistently followed by positive investor reactions, suggesting that GCG implementation is not always directly proportional to market perception. Furthermore, the unique characteristics of the banking sector, such as strict regulation and high dependency on public trust, demand focused research. This study aims to analyze the influence of corporate governance structure, measured by the number of board of directors (X1), board of commissioners (X2), and audit committee (X3), on investor reaction in banking companies listed on the Indonesia Stock Exchange (IDX). Employing a causal quantitative approach and multiple regression analysis on a sample of 46 banking companies from 2020–2024, the study found that the number of board of directors (X1) has a positive and significant effect on investor reaction. Conversely, the number of board of commissioners (X2) and the number of audit committee (X3) also have a significant partial effect, but the direction of influence is negative, contradicting the initial positive prediction. Simultaneously (F-test), all independent variables significantly affect investor reaction. This finding contributes to the understanding that certain GCG components, specifically the board of directors' size, provide a stronger positive signal to the market in the Indonesian financial context.